Factors Affecting Mortality in COVID-19 Pneumonia Patients Treated with Tocilizumab - Günaydın, Selda; Bektaş Aksoy, Hayriye; Aksoy, İskender; Elmas, Abdülbaki; Dülger, Ahmet Cumhur (The European Research Journal, 2026)
Objective: Severe COVID-19 pneumonia is often complicated by hyperinflammation and multiorgan failure. Tocilizumab, an interleukin-6 receptor antagonist, has been used to mitigate cytokine storm; however, it’s prognostic impact remains uncertain. Methods: This retrospective cohort study included 43 adult patients with PCR-confirmed COVID-19 pneumonia who received tocilizumab at a tertiary hospital in Turkiye between April and September 2020. Patients were categorized as survivors or non-survivors. Demographic data and laboratory markers were analyzed at baseline, 24 hours, and 7 days post-treatment. Statistical analyses included Mann–Whitney U, Wilcoxon signed-rank, and chi-square tests. Results: Non-survivors were significantly older (mean age: 72.4 vs. 64.9 years, P=0.046) and had higher levels of C-reactive protein (P=0.002), D-dimer (P=0.004), procalcitonin (P= 0.001), troponin (P=0.004), BUN (P